Prosedur Pengembangan Kurikulum Muatan Lokal Baca Tulis Al-Qur’an Tingkat Pendidikan Dasar dan Menengah di Kabupaten Pasuruan - Muhamad Mukhlason (Bidayatuna, 2021)
The Local Content Curriculum for Reading and Writing Al-Qur'an (BTQ) is a Local Content Curriculum developed by the Pasuruan Regency Government. The BTQ Local Content Curriculum has been implemented in primary and secondary education since the 2007/2008 school year until now. The length of time the implementation of the BTQ Local Content Curriculum indicates that the BTQ Local Content Curriculum has a very good quality. The quality of implementing a curriculum certainly cannot be separated from good curriculum development planning as well. This study aims to determine the steps to develop a Local Content Curriculum for Reading and Writing Al-Qur'an in Pasuruan Regency. Researchers used a qualitative approach in this research activity. The type of qualitative research used is a case study. This study found 3 main steps and several supporting steps used by the Pasuruan Regency Government in developing the Local Content Curriculum for Reading and Writing Al-Qur'an, namely: 1) planning through identifying the conditions and needs of the Pasuruan Regency area, and establishing a juridical basis, 2) organizing and implementation through the formation of the BTQ Local Content Curriculum development team, preparing the BTQ Local Content Curriculum Design, the preparation of the BTQ Mulok Technical Instructions and Implementation Guidelines, the BTQ MGMP formation for all levels of SD/MI, SMP/MTS, and SMA/SMK/MA, 3 ) evaluation includes process evaluation, result evaluation, and program evaluation. By knowing the steps for developing the Local Content Curriculum for Reading and Writing Al-Qur'an in Pasuruan Regency, students, teachers, and other local governments are expected to be able to duplicate and implement it in other areas that have the same culture as Pasuruan Regency.